Digital Marketing Sebagai Pengungkit Kinerja UMKM - Yuswono, Irawan; Turmudhi, Anis; Ristianawati, Yuyun; Praptitorini, Mirna Dyah; Salim, Noor (Jurnal Pengabdian Masyarakat Akademisi, 2024)
This activity aims to strengthen the abilities and skills of MSME (Micro, Small, and Medium Enterprises) actors in using digital technology to market their products and services. Through outreach, practical training, and the development of business groups, it is expected that MSME actors can develop more effective marketing strategies, enhance their competitiveness, and drive the economic growth of the village. The outreach discusses the importance of digital marketing, the latest trends, and its benefits for MSMEs. The practical training includes social media management, promotional content creation, paid marketing, and the creation and analysis of data for marketing purposes. The development of business groups aims to build cooperation and solidarity among MSME actors in developing joint digital marketing strategies. The results of the activities show an increase in participants' knowledge and skills and the formation of a solid network of cooperation among MSME actors.